1978
DOI: 10.1073/pnas.75.7.3099
|View full text |Cite
|
Sign up to set email alerts
|

ATP-induced conformational changes in the restriction endonuclease from Escherichia coli K-12.

Abstract: ATP induces a conformational change in the Escherichia coli K-12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 12 publications
4
41
0
Order By: Relevance
“…When the distance between a pair of sites was increased from 0.4 to 2.4 kb, the distribution of random cleavages between the sites expanded accordingly (Figure 4). Random cleavage has been observed between pairs of sites separated by as little as 100 bp and as much as 7 kb (Adler & Nathans, 1973;Bickle et al, 1978;Rosamund et al, 1979;Yuan et al, 1980;Dryden et al, 1997). Overall, our data for random cleavages on linear DNA concur with the collision model of Studier & Bandyopadhyay (1988).…”
Section: Random and Localised Cleavages By Ecor124imentioning
confidence: 91%
“…When the distance between a pair of sites was increased from 0.4 to 2.4 kb, the distribution of random cleavages between the sites expanded accordingly (Figure 4). Random cleavage has been observed between pairs of sites separated by as little as 100 bp and as much as 7 kb (Adler & Nathans, 1973;Bickle et al, 1978;Rosamund et al, 1979;Yuan et al, 1980;Dryden et al, 1997). Overall, our data for random cleavages on linear DNA concur with the collision model of Studier & Bandyopadhyay (1988).…”
Section: Random and Localised Cleavages By Ecor124imentioning
confidence: 91%
“…An alternative explanation for the preponderance of single loops might be that the enzyme remains bound to DNA at both translocation points but not at its recognition site. This seems less likely, however, because both EcoK and EcoB appear to remain bound at the recognition site after reacting (in the presence of ATP) with linear DNAs that have a single recognition site (12,14).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work on EcoB and EcoK has been interpreted to mean that the enzymes remain bound at their recognition site throughout the reaction and translocate DNA past themselves for long distances to reach their cleavage sites, forming simple or supertwisted loops in the process (9,(12)(13)(14). It was further concluded that EcoB can translocate DNA from only one side of the asymmetric recognition sequence (the 5' side, as usually written) (9) and that EcoK is capable of translocating DNA from either side (13); but the mechanism for selecting cleavage sites remained a mystery.…”
Section: Methodsmentioning
confidence: 99%
“…The restriction pathway is presumed to be initiated by the ATP-dependent conformational change originally reported for EcoKI (19) but analyzed only recently by footprinting (137). EcoKI remains the best-studied R-M complex in terms of sequence-specific binding, the effect of the cofactor AdoMet on representatives of the type IB and IC enzymes being less easy to assess because it is difficult to separate AdoMet from these enzymes (41, 133; P. Janscak and T. A. Bickle, personal communication).…”
Section: R-m Complexmentioning
confidence: 99%